2016
DOI: 10.1161/circimaging.115.003792
|View full text |Cite
|
Sign up to set email alerts
|

Unique Abnormalities in Right Ventricular Longitudinal Strain in Systemic Sclerosis Patients

Abstract: Background Cardiac involvement in systemic sclerosis (SSc) adversely affects long-term prognosis, often remaining undetectable despite close clinical examination and 2D echocardiographic monitoring. Speckle derived strain of the right ventricle (RV) was utilized to detect occult abnormalities in regional and global contractility in SSc patients. Methods and Results 138 SSc patients with technically adequate echocardiograms were studied, and compared with 40 age- and gender-matched healthy non-SSc controls. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
3
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 40 publications
3
62
3
3
Order By: Relevance
“…We previously demonstrated a heterogeneous pattern of RVLSS in a large cohort of SSc patients in which there was increased contractility of the basal RV free wall and diminished contractility of the midventricular and apical segments [8]. Here, we similarly demonstrated regional heterogeneity in which midventricular and apical segments had decreased RVLSS compared with the basal RV segment.…”
Section: To the Editorsupporting
confidence: 62%
See 1 more Smart Citation
“…We previously demonstrated a heterogeneous pattern of RVLSS in a large cohort of SSc patients in which there was increased contractility of the basal RV free wall and diminished contractility of the midventricular and apical segments [8]. Here, we similarly demonstrated regional heterogeneity in which midventricular and apical segments had decreased RVLSS compared with the basal RV segment.…”
Section: To the Editorsupporting
confidence: 62%
“…Speckle-tracking echocardiography (STE), an echo-based imaging modality used in conjunction with 2DE, allows offline calculation of myocardial velocities and deformation parameters in the assessment of regional myocardial contractility [7]. Our group recently demonstrated a heterogeneous pattern of RV longitudinal systolic strain (RVLSS) utilising STE in SSc patients with variable afterloads, which was not appreciable by 2DE alone [8]. Our findings, however, were shown in a cross-sectional analysis of asymptomatic SSc patients without symptomatic RV failure, right heart catheterisation (RHC)-confirmed PAH or with echocardiographic evidence of RV dilatation.…”
Section: To the Editormentioning
confidence: 99%
“…To date, different ultrasound Right Ventricular Strain in Systemic Sclerosis manufacturers and software developers have used different approaches (ie, definitions of the region of interest and of strain parameters) to 2DE image postprocessing to obtain strain and strain-rate values. The RVFWLS values reported by Mukherjee et al 3 in their control subjects are significantly lower than those reported in the literature. 5,9 However, they used a novel vendor-independent software package (EchoInsight, Epsilon Imaging, Ann Arbor, MI) to measure RVFWLS, whereas the large majority of investigators who applied RVFWLS for RV analysis used a different software (EchoPac, GE Vingmed, Horten, Norway).…”
Section: See Article By Mukherjee Et Alcontrasting
confidence: 70%
“…Mechanical dispersion was expressed by the standard deviation of the time from R on ECG to peak strain in 16 LV segments . Measurements from the RV included proximal RVOT diameter from the parasternal short‐axis view, basal RV diameter, tricuspid annular plane systolic excursion, and RV longitudinal strain (RVLS) calculated from three free wall RV segments …”
Section: Methodsmentioning
confidence: 99%